Adaptasi Alat Ukur Psikometri Lovingkindness Compassion versi Bahasa Indonesia - Fadliah Tri Kusnanda; Larasati Khairunnisa; Nur Huda Linnas; Restu Ainun Nissa Ainun; Ruth Agestianti; Helli Ihsan; Diah Zaleha Wyandini; Ghinaya Ummul Mukminin (Universitas Kristen Maranatha, 2024)
Academic stress has become a common experience among students. Prolonged academic stress can have negative consequences, one of which is the disruption of students' mental health. Lovingkindness Compassion is one of the active protectors of mental health for students. However, there has been no research on the measurement of Lovingkindness in Indonesia. Therefore, this study aims to test the validity and reliability of the Lovingkindess Compassion measurement tool adapted from Cho (2018). The Lovingkindeness Compassion scale consists of 15 items with 3 dimensions: compassion, self-centeredness, and lovingkindness. The subjects of this study were 214 active students in Bandung. The results of confirmatory factor analysis show that the model fits with the goodness-of-fit indices of 0.051 (RMSEA), 0.060 (SRMR), and 0.869 (CFI). The results of the confirmatory factor analysis test show that the model fits with fit index values ​​of 0.051 (RMSEA), 0.060 (SRMR), and 0.869 (CFI), so that the Lovingkindness Compassion measuring tool adapted to Indonesian is valid. Furthermore, the reliability test with Cronbach's Alpha coefficient yielded a result of 0.574, indicating that the measurement tool is reliable in the moderate category.